2014
DOI: 10.1097/rli.0b013e3182a71c5d
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fat Saturation Techniques for Single-Shot Fast Spin Echo Sequences for 7-T Body Imaging

Abstract: Of the compared techniques, the most favorable was SSGR because, here, a homogeneous FS with moderate tissue signal loss of approximately 20% was achieved with no additional preparation pulses being necessary. Using this FS technique combined with TIAMO image acquisition, delineation between fat and bright liquids in single-shot fast spin echo images, which is essential for diagnosis, is possible at 7 T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Though recent methodological developments regarding transmit strategies and SAR supervision enabled the exploitation of the potential of whole-body imaging at ultra-high field MRI, few studies reported the investigations about T2-weighted abdominal imaging [13,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though recent methodological developments regarding transmit strategies and SAR supervision enabled the exploitation of the potential of whole-body imaging at ultra-high field MRI, few studies reported the investigations about T2-weighted abdominal imaging [13,28].…”
Section: Discussionmentioning
confidence: 99%
“…SAR restrictions on the one hand and the limited available RF peak power available for achieving the large flip angles needed for spin echo imaging on the other hand are unsolved challenges [ 27 ]. Though recent methodological developments regarding transmit strategies and SAR supervision enabled the exploitation of the potential of whole-body imaging at ultra-high field MRI, few studies reported the investigations about T2-weighted abdominal imaging [ 13 , 28 ]. Our results, in accordance with previous comparison studies, showed that susceptibility artifacts and B1 inhomogeneities of T2-weighted images were significantly increased as compared to lower field strengths [ 12 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is challenging, though, to incorporate fat–water separation into FSE commonly used for diagnostic T 2 weighted liver and abdominal imaging, which requires uniform fat suppression. To address this issue, a slice‐selective gradient reversal technique was applied, which provided uniform fat suppression with moderate tissue signal loss of approximately 20% . This approach was combined with the time‐interleaved acquisition of modes (TIAMO) technique , which facilitated delineation between fat and bright liquids in single‐shot FSE .…”
Section: Applications and Clinical Opportunitiesmentioning
confidence: 99%
“…To address this issue, a slice‐selective gradient reversal technique was applied, which provided uniform fat suppression with moderate tissue signal loss of approximately 20% . This approach was combined with the time‐interleaved acquisition of modes (TIAMO) technique , which facilitated delineation between fat and bright liquids in single‐shot FSE . The progress in FSE imaging of the liver at 7.0 T opens opportunities for DWI of the liver free of geometric distortion, which is elusive for DWI‐EPI (echo planar imaging) because of susceptibility induced distortions.…”
Section: Applications and Clinical Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation